Evaluación de riesgos laborales y su incidencia en la elaboración de profesiogramas en la actividad agrícola de la Empresa Palmeras de los Andes S.A. - Vélez Macías, Moncerrate Argentina (2015)
In Ecuador most companies do not use job profiles and consider safety and health at work is limited to providing staff teams or individual protection but this interdisciplinary branch of engineering goes further, devoting time and effort to identify, measure , evaluation, control and monitoring of those environmental factors or stresses caused by the workplace. . The job profiles not apply in the Province of Esmeraldas and recently the Labor Ministry has emphasized that these are made in companies as part of the management of human resources. Through this investigation is to assess the risks of working in the company found Palmeras de Los Andes SA and to design job profiles that serve as technical and organizational guidance and contribute to the analysis of the job, all with the desire to date the company has identified and assessed risks in agricultural activity which does most working population.